Knowledge and self-care practices regarding diabetes among newly diagnosed type 2 diabetics in Bangladesh: a cross-sectional study - Saleh Farzana; Mumu Shirin J; Ara Ferdous; Begum Housne A; Ali Liaquat (BMC, 2012)
Abstract Background Levels of knowledge about diabetes mellitus (DM) among newly diagnosed diabetics in Bangladesh are unknown. This study assessed the relationship between knowledge and practices among newly diagnosed type 2 DM patients. Methods Newly diagnosed adults with type 2 diabetes (N = 508) were selected from 19 healthcare centers. Patients' knowledge and self-care practices were assessed via interviewer-administered questionnaires using a cross-sectional design. Knowledge questions were divided into basic and technical sections. Knowledge scores were categorized as poor (<mean - 1 SD), average (mean ± 1 SD), good (>mean + 1 SD). Chi square testing and multivariate logistic regression were conducted to examine the relationship between diabetes-related knowledge and self-care practices. Results Approximately 16%, 66%, and 18% of respondents had good, average, and poor (GAP) basic knowledge respectively and 10%, 78%, and 12% of respondents had GAP technical knowledge, about DM. About 90% of respondents from both basic and technical GAP did not test their blood glucose regularly; a significant relationship existed between basic knowledge and glucose monitoring. Technical knowledge and foot care were significantly related, though 81% with good technical knowledge and about 70% from average and poor groups did not take care of their feet. Approximately 85%, 71%, and 52% of the GAP technical knowledge groups, consumed betel nuts; a significant relationship existed between technical knowledge and consumption of betel nuts. Around 88%, 92%, and 98% of GAP technical knowledge groups failed to follow dietary advice from a diabetes educator. About 26%, 42%, and 51% of GAP basic and technical sometimes ate meals at a fixed time (p < 0.05). Approximately one-third of respondents in each basic knowledge group and 29%, 32%, and 32% of GAP technical knowledge groups partially followed rules for measuring food before eating. Total basic knowledge (TBK) and business profession were significant independent predictors of good practice. OR for TBK: 1.28 (95% CI: 1.03 to 1.60); OR for business profession 9.05 (95% CI: 1.17 to 70.09). Conclusions Newly diagnosed type 2 diabetics had similar levels of basic and technical knowledge of DM. Health education and motivation should create positive changes in diabetes-control-related self-care practices.